A conceptual framework for students’ data-driven decision making process in higher education institutions - Akanmu, Semiu Ayobami; Jamaludin, Zulikha (American Scientific Publishers, 2015)
With the increase in volume and the wide range of data needed to inform decisions at all levels of education system, federal and state ministries of education, districts and also schools have been demanding proactive and data-driven decision making (DDDM) frameworks, as an approach to enhance policy and decision making.In dealing with DDDM, higher education institutions (HEI), among schools, are found to be the most in need of such decision-support frameworks, because of the volume of the data they deal with, and the sensitivities of the decisions they make.To attend to this, though with an exclusive focus on the HEI’s students, we propose a DDDM conceptual framework, using a Design Research Method.The method includes critical literature review, survey instrument administration on the HEI policymakers, and interview sessions with data management personnel. Our proposed conceptual framework shows (1) how DDDM can achieve effective students’ data usage and improved students-related decision making, (2) HEI decision makers’ data usages, their preferred explicit knowledge from the data, and the relationship with the appropriate data variables.